JAWA BANTEN LANGUAGE IN CLASSROOMS: A CHALLENGE OR A PROBLEM? - Siti Suharsih (Kantor Bahasa Provinsi Banten and Perkumpulan pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya (PPJB-SIP)., 2016)
The existence of JawaBanten language and other languages in Banten contributes in making Banten as a multilingual community. As the result, the speakers of JawaBanten language have to choose the appropriate language to be spoken based on the participants , topic and the objective of their speaking. If the speakers of JawaBanten language frequently use dominant language, such as Bahasa Indonesia, Sundanese, and English in their community, the process of shifting language is happened. Therefore, schools have important role in promoting JawaBanten language by teaching it as local content, and it become oneof local government effort to protect the local language. In line with that, this paper aims to describe JawaBanten language that is used in the classrooms as local content. To explain the teaching application of JawaBanten language in classrooms, researcher conducted the research in some state schools in Serang which have implemented JawaBanten language as local content. Data was presented qualitatively after distributing questionaire to students and interviewing the teacher. This research was expected showing the fact of how the implementation of teaching JawaBanten language in the classroom.The result of the questionaire and interview hopefully will give recommendation for policy maker (local government) to make new resolution for protecting Jawa Banten language as local language.